2020
DOI: 10.15446/cuad.econ.v39n81.77333
|View full text |Cite
|
Sign up to set email alerts
|

Etnicidad, espacio y desarrollo humano en comunidades pobres urbanas: la comuna 6 en Cartagena de Indias, Colombia

Abstract: Cartagena de Indias registra la mayor exclusión social entre las principales ciudades colombianas. Este artículo evalúa el nivel de desarrollo humano y los determinantes de la pobreza en la comuna 6, donde predomina la población afrocolombiana. Con el marco analítico de pobreza urbana, capacidades y estructura de oportunidades, y una base ad hoc para estimar un modelo probit como estrategia empírica, se elabora un perfil de pobreza diferenciado para esta extensa zona, con un enfoque espacial. Los resultados mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…Regarding carnival, studies have been proposed mainly from disciplines such as anthropology (M. Abello et al, 2005;de Friedemann, 1984;Lizcano & Gonzalez, 2007;Mariano & Endere, 2017), sociology (González, 2006;Rey Sinning, 2004;Reyes, 2011), communication and musicology (Carbó, 1993;Espinosa & Seni, 2019;Ochoa, 2015), among others.…”
Section: Studies In Colombia: Cultural Participation and Carnivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding carnival, studies have been proposed mainly from disciplines such as anthropology (M. Abello et al, 2005;de Friedemann, 1984;Lizcano & Gonzalez, 2007;Mariano & Endere, 2017), sociology (González, 2006;Rey Sinning, 2004;Reyes, 2011), communication and musicology (Carbó, 1993;Espinosa & Seni, 2019;Ochoa, 2015), among others.…”
Section: Studies In Colombia: Cultural Participation and Carnivalmentioning
confidence: 99%
“…This model also allows for the adequate inclusion of qualitative variables and the identification of inputs for territorial public policies. In addition, it has an advantage over other discrete choice models such as the linear probability model (MPL) in terms of the variance term (homoscedasticity), no bounding of the estimates and no underestimation of the parameters (Espinosa, Madero, Rodriguez-Puello, & Diaz, 2020).…”
Section: Empirical Strategymentioning
confidence: 99%
“…Hence, preserving environmental habitats is crucial for economic development and human survival. The seminal work by Werner (1787), who laid the foundation of early geology, discussed the Earth's origin (Chena et al, 2020;Cómbita Mora, 2020;Espinosa-Espinosa et al, 2020;Sorokhtin et al, 2011). Basic research concerning the Earth revealed that, during a certain period, it was inhabitable due to high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, en Colombia las desigualdades también se manifiestan en brechas locales y regionales (Galvis & Meisel, 2013;Espinosa et al, 2020) que afectan el bienestar de las personas: el capital humano, la ocupación del territorio, la posesión de activos productivos, el acceso a la seguridad y el hábitat. Por ello es pertinente preguntarse si también estas diferencias se manifiestan en la participación en actividades deportivas que, junto a otras actividades de ocio como la cultura (Espinosa & Palma, 2019), es una de las dimensiones del bienestar menos estudiadas en este país y en América Latina.…”
Section: Introductionunclassified